2010
DOI: 10.2754/avb201079s9s107
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Biogenic Amines in Chicken Meat Stored under Modified Atmosphere

Abstract: The aim of the study was to investigate the effects of two modified atmospheres with a different combination of gases on selected groups of microorganisms and on concentrations of biogenic amines (BAs) in samples of poultry breast muscle. The samples were packaged under modified atmosphere A (75% O 2 a 25% CO 2 ) or B (75% N 2 and 25% CO 2 ) and stored at temperatures from +2 to +4 °C for 14 days. During the storage period, O 2 concentrations in modified atmosphere A (MA A) decreased from the initial 74.8 ± 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 28 publications
(41 reference statements)
0
19
0
Order By: Relevance
“…Gallas et al . () suggested that the development of microflora with decarboxylase activity begins only after some days of storage, when other BAs began to be produced by microbial action.…”
Section: Resultsmentioning
confidence: 97%
“…Gallas et al . () suggested that the development of microflora with decarboxylase activity begins only after some days of storage, when other BAs began to be produced by microbial action.…”
Section: Resultsmentioning
confidence: 97%
“…Production of biogenic amines in foods is associated with the presence of microorganisms and their activity in food (Halász et al 1994). The monitoring of biogenic amine concentrations is very important because, from the human health point of view, their presence in food at elevated concentrations has been involved in various cases of foodborne diseases and cases of human poisoning (Shalaby 1996), and has been associated with negative effects on human heath (Balamatsia et al 2006;Gallas et al 2010;Naila et al 2010;Standarová et al 2012) and various other toxicological effects (Hernández-Jover et al 1997).…”
mentioning
confidence: 99%
“…The residual oxygen percent available inside of the packages submitted to a modified atmosphere decreased during storage and reached values below 1% at the end of the storage period for all of the treatments with Co 2 . This result is related to the fact that most microorganisms present in meat, such as Brochothrix thermosphacta and LAB, which produce carbon dioxide as a metabolite (Nychas, 1994;Patsias et al, 2006;Gallas et al, 2010), use the available residual oxygen. In addition, meat biochemical activity and plastic impermeability help to maintain the reduced o 2 concentration inside the packages (Mano et al, 2002).…”
Section: Resultsmentioning
confidence: 85%